HPLC-investigations of imidazoquinazolone derivatives. Part 2 - Szász, G; Budváriné-Bárány, Z; Löre, A; Kökösi, J; Orfi, L (Acta pharmaceutica Hungarica, 1991)
In a previous paper (2) authors, reported good correlation between the HPLC (log k') and TLC (RM) retention data and the 1-octanol/water partition coefficient (log l') of imidazoquinazolone derivatives synthetized in their laboratory. In the present work the behaviour of the compounds in HPLC systems containing ion-pairing agents (camphorsulfonic acid, Na-dodecyl sulfate) has been studied. While, in reversed phase systems no change of retention indicating the formation of ion-pairs or molecule complexes was observed, camphor-sulfonic acid caused significant increase of retention in the chromatographic systems with bare silica as stationary phase. This phenomenon is interpreted by the formation of camphorsulfonic acid double layer on the silica surface and as a consequence of mixed retention mechanism. The results of a detailed study on the latter subject will be published in a next paper. Double peak formation was observed in reversed phase system in case of C1-C3 disubstituted derivatives. This was interpreted with the formation of isomeric mixtures. Theoretical considerations as well as the identical spectra of the two peaks make plausible the appearance and separation of conformational isomers.